THE ROLE OF HISTORICAL MEMORY IN THE STUDY OF SOCIO-PHILOSOPHICAL HERITAGE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article reveals the importance of historical memory in the study of socio-philosophical heritage. At the same time, the interrelationship with the concepts of nation, people, socio-spiritual environment is highlighted in the historical memory. In this case, the role of incentives is correctly indicated.